Quantitative research on the EFQM excellence model: A systematic literature review (1991-2015) - Eva Suárez; Arturo Calvo-Mora; José L. Roldán; Rafael Periá\~nez-Cristóbal (European Research on Management and Business Economics (ERMBE), 2017)
The purpose of the paper is to present the state of the art in quantitative research on the EFQM modelthat will guide future research lines in this field. For this, a systematic literature review from the period 1991–2015 is carried out in impact journals belonging to the Journal Citation Reports (JCR) and SCImagoJournal & Country Rank (SJR). Finally, 53 papers were selected and aspects related to the purpose, nature and instruments of data collection, type of quantitative analysis employed, sector under study and main conclusions and contributions are analysed. As a result, the study presents more than a dozen lines of future research.
Keywords: C18; M10; M19; 650; EFQM model; Excellence models; Quantitative research; Systematic literature review